2007
DOI: 10.1158/1055-9965.epi-07-0566
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Physical Activity and Epithelial Ovarian Cancer: A Case-Control Study, Systematic Review, and Meta-analysis

Abstract: It remains unclear whether physical activity is associated with epithelial ovarian cancer risk. We therefore examined the association between recreational physical activity and risk of ovarian cancer in a national population-based case-control study in Australia. We also systematically reviewed all the available evidence linking physical activity with ovarian cancer to provide the best summary estimate of the association. The case-control study included women ages 18 to 79 years with a new diagnosis of invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 55 publications
2
101
0
1
Order By: Relevance
“…We aimed for similar numbers of male cases and controls in each stratum of age and state; female controls were intentionally oversampled at all ages to accommodate their simultaneous enrollment in a parallel case-control study of ovarian cancer (48). Of 3,258 potentially eligible control participants who were contacted and invited to participate, 175 were excluded because they were deceased (16), too ill (61), or unable to read or write in English (98), and 41 were lost to follow-up in the interval between initial contact and participation.…”
Section: Methodsmentioning
confidence: 99%
“…We aimed for similar numbers of male cases and controls in each stratum of age and state; female controls were intentionally oversampled at all ages to accommodate their simultaneous enrollment in a parallel case-control study of ovarian cancer (48). Of 3,258 potentially eligible control participants who were contacted and invited to participate, 175 were excluded because they were deceased (16), too ill (61), or unable to read or write in English (98), and 41 were lost to follow-up in the interval between initial contact and participation.…”
Section: Methodsmentioning
confidence: 99%
“…Evidências disponíveis indicam que a exposição a baixos níveis de atividade física constitui fator de risco para doenças crônicas não transmissíveis, como a obesidade, o diabetes, as doenças cardiovasculares e certos tipos de neoplasias (MONNINKHOF et al, 2007;NOCON et al, 2008;OLSEN et al, 2007;QIN et al, 2010;WAREHAM et al, 2005). Apesar do reconhecimento quanto à importância que as atividades físicas podem desempenhar na prevenção de doenças e melhoria da qualidade de vida, estudos têm relatado uma elevada prevalência de níveis insuficientes de prática de atividades físicas em todos os grupos populacionais, inclusive entre crianças e adolescentes (BASTOS et al, 2008;HOELSCHER et al, 2009).…”
Section: Introductionunclassified
“…More than 20 studies have been conducted on physical activity and ovarian cancer demonstrating inconsistent findings (Olsen et al, 2007;WCRF/AICR, 2007;Friedenreich et al, 2010a;Speck et al, 2011). The reviews concluded that there was a modest inverse relationship between physical activity and ovarian cancer development with about 10-20% reduction of the risk.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Estimation of a dose-response trend showed inconsistency for all types of activity, i.e. the beneficial effect of physical activity was somewhat stronger for recreational activity than occupational activity (Olsen et al, 2007). It is worthwhile to add that two studies (Zhang et al, 2004, Patel et al, 2006 reported about 50% increase in ovarian cancer risk among women sitting ≥6 hours daily.…”
Section: Ovarian Cancermentioning
confidence: 99%